Strategi Manajemen Pemasaran Pendidikan Berbasis Media Sosial dalam Menarik Mahasiswa Baru Universitas Primagraha - Riki Gana Suyatna; Surya Alam; Nurmala Vinata Putri (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Primagraha University, like other private educational institutions, is faced with the task of attracting the attention of prospective new students amidst increasingly fierce competition. The use of social media as an educational marketing tool provides a unique opportunity to interact directly with prospective students, build brand awareness, and promote university excellence. Education marketing is a strategic approach in managing information and image of educational institutions to attract new students. This research aims to describe an overview of the management of educational marketing strategies using social media at Primagraha University. This type of research uses Field Research. The research uses qualitative methods with data collection techniques carried out through interviews, documentation and social media content analysis. The most effective social media used in the educational marketing process include 3, namely: Instagram, YouTube, and websites. The content presented is in the form of academic activities, promotions, information regarding new student admissions, campus activities, and student achievements. The research results show that implementing marketing strategies using social media has a very good impact on the interest of new students.